Four-dimensional flow magnetic resonance assessment of alcohol septal ablation for hypertrophic obstructive cardiomyopathy and surgical valve replacement for aortic valve stenosis - Aoyama, Rie; Okino, Shinichi; Fukuzawa, Shigeru (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertrophic cardiomyopathy sometimes complicates left ventricular (LV) outflow tract obstruction. Alcohol septal ablation (ASA) is indicated for drug-refractory hypertrophic obstructive cardiomyopathy (HOCM). Moreover, with an aging population, aortic valve stenosis (AS) is increasing, and surgical aortic valve replacement (SAVR) is indicated in these cases. Both AS and HOCM have stenosis at the exit of the LV and there is a difference in valvular and/or muscular stenosis. However, it is not clear how the release of stenosis affects blood flow. We investigate the influence of ASA and SAVR on blood flow using four-dimensional flow phase-contrast magnetic resonance imaging (4D flow MRI).MethodsIn this single-center retrospective observational study, we evaluated the blood flow of eight patients (five patients with HOCM and three patients with AS) before and after the intervention using 4D flow MRI.ResultsThe LV-aortic pressure gradient (PG) significantly improved from 79.4 ± 3.9 to 23.0 ± 2.0 mmHg (p < 0.001) by SAVR in the patients with AS. However, turbulent kinetic energy value (TKE) loss was not improved. However, the intra-LV PG in patients with HOCM improved from 79.0 ± 54.2 to 8.7 ± 4.0 mmHg (p < 0.05) by ASA. TKE loss improved from 7.0 ± 2.0 to 5.0 ± 0.1 mW (p < 0.05) and New York Heart Association functional class significantly improved from 2.2 ± 0.5 to 1.1 ± 0.3 (p < 0.001) by ASA.ConclusionsThe release of valvular or muscular stenosis has different effects on intra-LV blood flow. ASA reduced TKE loss and 4D flow MRI is useful to evaluate the efficacy of therapeutic interventions.